2016
DOI: 10.3390/ma9100845
|View full text |Cite
|
Sign up to set email alerts
|

Modification of Lightweight Aggregates’ Microstructure by Used Motor Oil Addition

Abstract: An admixture of lightweight aggregate substrates (beidellitic clay containing 10 wt % of natural clinoptilolite or Na-P1 zeolite) with used motor oil (1 wt %–8 wt %) caused marked changes in the aggregates’ microstructure, measured by a combination of mercury porosimetry (MIP), microtomography (MT), and scanning electron microscopy. Maximum porosity was produced at low (1%–2%) oil concentrations and it dropped at higher concentrations, opposite to the aggregates’ bulk density. Average pore radii, measured by M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 38 publications
1
6
0
Order By: Relevance
“…Silica, phosphorus, aluminum and calcium oxides constituted the largest percentage in the fly ash oxide composition. It was observed that the sum of silica dioxide (25.54% of SiO 2 ), aluminum oxide (18.98% of Al 2 O 3 ) and iron oxide (7.77% of Fe 2 O 3 ) contents in FAMSS was lower than in conventional ashes, and did not meet the requirements of the PN-EN 450-1 + A1: 2012 standard (minimum 65% total) [46], which is consistent with the results obtained for FAMSS produced in May 2017 [29]. However, the sum of SiO 2 , Fe 2 O 3 and Al 2 O 3 contents in FAMSS from 2018 (52.29%) was higher than in FAMSS from 2017 (35.40%) tested by Rutkowska et al [28].…”
Section: Properties Of Fly Ash and Concrete MIXsupporting
confidence: 82%
“…Silica, phosphorus, aluminum and calcium oxides constituted the largest percentage in the fly ash oxide composition. It was observed that the sum of silica dioxide (25.54% of SiO 2 ), aluminum oxide (18.98% of Al 2 O 3 ) and iron oxide (7.77% of Fe 2 O 3 ) contents in FAMSS was lower than in conventional ashes, and did not meet the requirements of the PN-EN 450-1 + A1: 2012 standard (minimum 65% total) [46], which is consistent with the results obtained for FAMSS produced in May 2017 [29]. However, the sum of SiO 2 , Fe 2 O 3 and Al 2 O 3 contents in FAMSS from 2018 (52.29%) was higher than in FAMSS from 2017 (35.40%) tested by Rutkowska et al [28].…”
Section: Properties Of Fly Ash and Concrete MIXsupporting
confidence: 82%
“…Besides thermal regeneration [60], spent sorbents can be used as a substrate for the production of lightweight aggregates [72,73]. The utilization of spent adsorbents in this kind of application provides obtained aggregates with new properties, including higher porosity.…”
Section: Sorption Of Land-based Oil Spillsmentioning
confidence: 99%
“…The pore surface fractal dimensions calculated for all adsorbents but FA900 are higher than three, which is theoretically restricted. Such high "fractal dimensions" may result from the specific structure of the pores: if the large pores are accessible through narrower entrances, the large pore volume is attributed to the radius of the entrance and because all volume is treated as belonging to a long capillary in a cylindrical pore model, the dV/dR is also higher and gives D s values higher than three [68]. No evident trends were observed in changes in "mesopore surface fractal dimension" due to the adsorbents' treatment.…”
Section: Parametermentioning
confidence: 99%